If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -115 + -7x = 8x + -120 Reorder the terms: -115 + -7x = -120 + 8x Solving -115 + -7x = -120 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -115 + -7x + -8x = -120 + 8x + -8x Combine like terms: -7x + -8x = -15x -115 + -15x = -120 + 8x + -8x Combine like terms: 8x + -8x = 0 -115 + -15x = -120 + 0 -115 + -15x = -120 Add '115' to each side of the equation. -115 + 115 + -15x = -120 + 115 Combine like terms: -115 + 115 = 0 0 + -15x = -120 + 115 -15x = -120 + 115 Combine like terms: -120 + 115 = -5 -15x = -5 Divide each side by '-15'. x = 0.3333333333 Simplifying x = 0.3333333333
| 4(x+4)+x=3(x+2)-8 | | 7+f=4f+1 | | 4m=7m | | 24-(x+9)=6x-6 | | 2x^2+25x+63= | | 2x^5-10x^4+18x^3-18x^2+16x-8=0 | | 16=8(x-3) | | 3x+6p=4x-4p | | h(t)=1t^2+3.7t+352 | | -2(x+5)+5=6(x+4)+2 | | h(t)=1t^2+144t+352 | | -3(x+3)+3=5(x+4)+3 | | 6=-6x-36 | | x-1=-34 | | 6(x-8)+18=3(x-6) | | -18-19=x+7 | | 0.7x-0.7(6-x)=0.7 | | 2(x+3)+2(x-1)=(x+10) | | t-10=0 | | -8(4+9)=7(-2-11x) | | 18x-9-7x=-4x+36 | | 8x-2(4-x)=10 | | -5r+6=-5r+-10 | | y+12=12 | | 5x^2+3x-15=33-31x | | g-8=3 | | 4t+9=-8t-15 | | -1=x+4 | | 3x+6p-4x-4p= | | 35/5*3= | | c-5=7 | | 2t+3n=9 |